Peran Aplikasi Pegadaian Digital Service (PDS) dalam Mempermudah Transaksi dan Layanan Milenial di PT Pegadaian Sumbawa - Pratama, Ari; Rakhmatullah, Vivin Nila (Al-DYAS, 2024)
Pegadaian is a state-owned company that has been established since 1905 and is currently 123 years old. This company is one of the most developed companies in Indonesia, including in the city of Sumbawa, West Nusa Tenggara Province. This is indicated by the increasing number of branch offices and UPCs on the island of Sumbawa which are very easy to find. PT. Pegadaian continues to innovate pawn products to attract consumers and increase company profits. In line with this, the number of consumers has also increased drastically because of the various conveniences offered by PT. Pegadaian with the slogan "Solving problems without problems". This research aims to find out the role of the Pegadaian Digital Service (PDS) application in facilitating millennial transactions and services at Pt Pegadaian Sumbawa. This research uses a qualitative descriptive method based on primary and secondary data and uses data collection techniques: observation, interviews, and documentation. Data was analyzed interactively using steps, namely data reduction and data validity. The results of the research show that the role of the Pegadaian Digital Service (PDS) application in facilitating millennial transactions and services at PT Pegadaian Sumbawa is without effectiveness, weak effectiveness, hidden effectiveness, and premium effectiveness.